Chile harvesters in Santa Maria - Manuel Echavarria::::::photographer:::
The setback in Santa Maria's chile fields signaled a discouraging trend. Grower-influenced legislators would cut off funding o the Agricultural Labor Relations Board (ALRB), the agency created to enforce the state's new labor act, while growers used bureaucratic and legal maneuvers to undermine or delay implementing hard-won contracts. The UAW would turn to the ballot box for justice.